Can smiling influence the blood flow in the facial vein?—An experimental study. (10th December 2019) - Cotofana, Sebastian; Lowry, Natalia; Devineni, Aditya; Rosamilia, Gianna; Schenck, Thilo L.; Frank, Konstantin; Bautista, Sana A.; Green, Jeremy B.; Hamade, Hassan; Gotkin, Robert H.
Abstract: Background: The understanding of functional facial anatomy and the interplay between facial structures is crucial for safe and effective minimally invasive and cosmetic surgical procedures. Aim: In this experimental study, we investigate the hypothesis that smiling can alter the blood flow in the angular/facial vein. Materials and Methods: Twenty‐six observations from 15 healthy volunteers (6 men, 9 women) with a mean age of 50.53 ± 13.27 (range: 24‐66) were obtained. Doppler ultrasound imaging of the infraorbital segment of the angular vein (cranial to the zygomaticus major muscle) was performed and the venous flow was measured in a smiling and a resting, nonsmiling facial position. Results: A statistically significant change in venous blood flow was detected upon smiling: a reduction in flow from 6.12 ± 3.0 cm/s to 0.52 ± 1.3 cm/s ( P  = .001). After three seconds, 80.8% of the observations had a blood flow of 0.0 cm/s. Increasing age was significantly correlated with a persistent blood flow during smiling ( r p  = .469; P  = .016). No differences between gender and sides of the face were observed. Conclusion: The results of this experimental study reveal that smiling can significantly reduce the venous flow in the angular/facial vein. Contraction of the zygomaticus major muscle compresses the vein against the underlying maxilla. Both minimally invasive and surgical procedures that alter the SMAS, the periocular musculature or the deep midfacial fat compartments might affect angular/facial venous flow.